Effect of Graded Levels of Toasted Lima Bean (Phaseolus lunatus) Meal in Weaner Rabbit Diets - Akinmutimi, A.H.; Ezea, J. (Pakistan Journal of Nutrition, 2006)
Twelve rabbits were used to determine the effect of graded levels of toasted lima bean meal in weaner rabbit diets in a completely randomized design (CRD) experiment. There were four treatments in the experiment. Each was replicated thrice. Diet 1 (control) was lima bean-free while diets 2, 3 and 4 contained 25%, 30% and 35% levels of toasted lima bean meal, respectively. The experiment spanned 56 days, during which data were collected from the animals. There were significant (P< 0.05) differences in the growth performance parameters except for feed-to-gain ratio. The highest mean feed intake (42.35g) was obtained with diet 1 (0%) and was significantly (P< 0.05) different from diet 4 (35%) toasted lima bean meal only (35.61g). The mean weight gain followed similar pattern. There was no significant (P>0.05) difference in feed-to-gain ratios. The lowest ratio (2.34) was obtained with diet 2 (25%). Following are 2.36, 2.47 and 2.62 in diets 1, 3 and 4, respectively. Gross margin was highest (N1760.16) in diet 3. Next are N1757.35, N1744.38 and N1703.57 in diets 2, 1 and 4, respectively. There was no significant difference (P>0.05) among the values for cut-parts and organ weights. Considering the growth performance, carcass quality, organ weight and gross margin, it is concluded that toasted lima bean meal could be included up to 30% in weaner rabbits diet.